2015
DOI: 10.1080/08870446.2015.1014816
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of end-of-life fears in COPD – hoping for the best but preparing for the worst

Abstract: Administration and intensity of end-of-life care (especially concerning end-of-life fears) in COPD patients should be based not only on illness severity, but rather on psychological distress and disease-specific anxieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Research on hope in COPD is fairly limited and controversial (Stenzel, Vaske, Kuhl, Kenn, & Rief, 2015). Research by Robinson, Lucas, Van den Dolder, and Halcomb (2017) found that COPD patients did express some kind of hope about the future, although they also reported feelings of grief and loss related to their COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Research on hope in COPD is fairly limited and controversial (Stenzel, Vaske, Kuhl, Kenn, & Rief, 2015). Research by Robinson, Lucas, Van den Dolder, and Halcomb (2017) found that COPD patients did express some kind of hope about the future, although they also reported feelings of grief and loss related to their COPD.…”
Section: Discussionmentioning
confidence: 99%
“…We were also interested in knowing whether variables such as gender, depression or fear of death affect performance. Depression is often associated with physical illness (Ruttley & Reid, 2006) and with fear of death (Stenzel, Vaske, Kühl, Kenn, & Rief, 2015), and gender differences in diseases and health care (e.g., Denton, Prus, & Walters, 2004) can modulate memory and life-support preferences.…”
Section: Memory Of Medical Scenarios In the Life Support Preferences mentioning
confidence: 99%
“…Weiterhin ist nachweisbar, dass Depressionen mit einem höheren Risiko für häufigere Exazerbationen und Krankenhausaufenthalte verbunden sind [43]. Schließlich beeinflussen COPDspezifische Ängste zum einen die wahrgenommenen Einschränkungen durch die Erkrankung [23], zum anderen mediieren jene die Beziehung zwischen psychischen Belastungen und End-of-lifeÄngsten [46].…”
Section: Zusammenhänge Von Psychischen Symptomen Und Physischen Sowieunclassified